MicroRNA Theranostics in Prostate Cancer Precision Medicine. (6th January 2020) - Matin, Farhana; Jeet, Varinder; Clements, Judith A; Yousef, George M; Batra, Jyotsna
Abstract: BACKGROUND: Prostate cancer is the second most frequently diagnosed cancer in men worldwide. Theranostics, a combination of diagnostics and therapeutics, is an emerging concept in the field of precision medicine, and microRNAs (miRNAs) are predictive pioneers in this area. CONTENT: miRNAs are small endogenous noncoding RNA molecules that regulate gene expression posttranscriptionally by targeting messenger RNAs. More than 60% of all protein coding genes are controlled by miRNAs, which makes them powerful regulators of the different cellular processes involved in the pathogenesis of various types of cancer, including prostate cancer. Growing evidence indicates the differential expression of miRNAs in tumor tissues. In addition, miRNAs in body fluids, known as circulating miRNAs, are present in remarkably stable forms and their alteration in prostate cancer has been well documented. Circulating miRNAs are known to originate from tumor tissues, thereby enabling intercellular communication via carriers to promote tumorigenesis and malignancy. In addition, fueled by recent advances, the use of miRNA-based anticancer therapies has been proposed with the onset of early phase clinical trials to assess the therapeutic efficacy of miRNAs. SUMMARY: In this review, we summarize the theranostic utility of miRNAs and outline their diagnostic and prognostic potential in prostate cancer. In addition, we discuss the current detection methodologies and emerging innovative strategies for the detection of miRNAs in body fluids and tumor tissues in the clinical setting. We also provide insight into the current and future therapeutic potential of miRNAs in prostate cancer.